2021
DOI: 10.1016/j.xgen.2021.100064
|View full text |Cite
|
Sign up to set email alerts
|

PCR amplicons identify widespread copy number variation in human centromeric arrays and instability in cancer

Abstract: SUMMARY Centromeric α-satellite repeats represent ~6% of the human genome, but their length and repetitive nature make sequencing and analysis of those regions challenging. However, centromeres are essential for the stable propagation of chromosomes, so tools are urgently needed to monitor centromere copy number and how it influences chromosome transmission and genome stability. We developed and benchmarked droplet digital PCR (ddPCR) assays that measure copy number for five human centromeric arrays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…This enabled us to assess variability between centromeric regions in a diploid human genome. Consistent with prior studies 50-57 , we found that centromeric α-satellite higher-order repeat (HOR) arrays often vary in length by tens to hundreds of kilobases. For example, Figure 4 shows the centromeric HOR arrays from Chr19.…”
Section: Resultssupporting
confidence: 90%
“…This enabled us to assess variability between centromeric regions in a diploid human genome. Consistent with prior studies 50-57 , we found that centromeric α-satellite higher-order repeat (HOR) arrays often vary in length by tens to hundreds of kilobases. For example, Figure 4 shows the centromeric HOR arrays from Chr19.…”
Section: Resultssupporting
confidence: 90%
“…Second, SatDNA sequences are a fast-evolving genomic feature, and studies are limited by the species present in the literature, which may display a limited snapshot of SatDNA sequence evolution in Drosophila . Finally, considerable intraspecific SatDNA variation is observed in eukaryotic genomes ( Arora et al 2021 ; de Lima et al 2021 ), thus future population surveys of genome size variation and repeat composition may be necessary to completely understand the evolution of SatDNA in Drosophila . Our results help reveal how SatDNA evolved and are evolving within the Drosophila genus and serve as an important resource to improve analysis of SatDNA in Drosophila genome assemblies, comparative genomic analyses, and future functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…These satellite arrays are hypervariable in the human population and alterations in their activity have been linked to cancer [ 127 , 129 ]. The detection of copy number variation within long satellite DNA arrays is relatively complex and often requires development of new assays [ 130 ], such as nanoplate-based digital PCR. Further studies are necessary to reveal satellite DNAs and RNAs as potential diagnostic, prognostic or therapeutic cancer biomarkers.…”
Section: Satellite Dnas and Rnas As Cancer Biomarkersmentioning
confidence: 99%